Particularism for Generalists: A Rossian Business Ethic. Issue 4 (7th October 2021) - Drake, J.
Abstract : A standard framework for business ethics views the inquiry as an application of major ethical theories to specific issues in business. As these theories are largely presented as being principled, the exercise therefore becomes one of applying general principles to business situations. Many adopting this standard approach have thus resisted the implementation of the most prominent development in ethical theory in recent history: that of particularism. In this article, I argue that particularist thinking has much to offer to business ethics and that standard resistance to particularist business ethics is based largely on misunderstandings. I do so by illustrating how the harbinger of particularism, W. D. Ross, countenances the practical wisdom of particularist ethics while being 1) invulnerable to standard objections to particularist business ethics and 2) compatible with the generalism of the standard approach. The Rossian business ethic is therefore one that the standard approach should be eager to include.